2015
DOI: 10.5455/aim.2015.23.172-176
|View full text |Cite
|
Sign up to set email alerts
|

Information Retrieval in Telemedicine: a Comparative Study on Bibliographic Databases

Abstract: Background and Aims:The first step in each systematic review is selection of the most valid database that can provide the highest number of relevant references. This study was carried out to determine the most suitable database for information retrieval in telemedicine field.Methods:Cinhal, PubMed, Web of Science and Scopus databases were searched for telemedicine matched with Education, cost benefit and patient satisfaction. After analysis of the obtained results, the accuracy coefficient, sensitivity, unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The PubMed and Web of Science databases are well established and frequently used in medical and related research fields. Moreover, they have also been recommended for searching telemedicine-related studies [ 37 ]. In addition, the PsycInfo database was included to account for the mental health context.…”
Section: Methodsmentioning
confidence: 99%
“…The PubMed and Web of Science databases are well established and frequently used in medical and related research fields. Moreover, they have also been recommended for searching telemedicine-related studies [ 37 ]. In addition, the PsycInfo database was included to account for the mental health context.…”
Section: Methodsmentioning
confidence: 99%
“…Users must know the source and explore various topics of interest. [15][16][17][18][19][20][21][22] However, some researchers have concluded that a single database is not sufficient to retrieve knowledge for users. Several referral systems for digital libraries have been proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even if search sessions are methodical and well documented, vendor systems often operate as black boxes (i.e., the technology is not well documented) and it becomes only possible to infer how different systems operate by comparing multiple implementations [ 37 ]. Little is known about what actual principles are applied by platform vendors in indexing bibliographic records or what specific types of algorithms are used to rank results when sorted by system-defined relevance.…”
Section: Introductionmentioning
confidence: 99%